Disability and health-related rehabilitation in international disaster relief - Reinhardt, Jan D.; Li, Jianan; Gosney, James; Rathore, Farooq A.; Haig, Andrew J.; Marx, Michael; Delisa, Joel A. (Global health action, 2011)
BackgroundNatural disasters result in significant numbers of disabling impairments. Paradoxically, however, the traditional health system response to natural disasters largely neglects health-related rehabilitation as a strategic intervention.ObjectivesTo examine the role of health-related rehabilitation in natural disaster relief along three lines of inquiry: (1) epidemiology of injury and disability, (2) impact on health and rehabilitation systems, and (3) the assessment and measurement of disability.DesignQualitative literature review and secondary data analysis.ResultsAbsolute numbers of injuries as well as injury to death ratios in natural disasters have increased significantly over the last 40 years. Major impairments requiring health-related rehabilitation include amputations, traumatic brain injuries, spinal cord injuries (SCI), and long bone fractures. Studies show that persons with pre-existing disabilities are more likely to die in a natural disaster. Lack of health-related rehabilitation in natural disaster relief may result in additional burdening of the health system capacity, exacerbating baseline weak rehabilitation and health system infrastructure. Little scientific evidence on the effectiveness of health-related rehabilitation interventions following natural disaster exists, however. Although systematic assessment and measurement of disability after a natural disaster is currently lacking, new approaches have been suggested.ConclusionHealth-related rehabilitation potentially results in decreased morbidity due to disabling injuries sustained during a natural disaster and is, therefore, an essential component of the medical response by the host and international communities. Significant systematic challenges to effective delivery of rehabilitation interventions during disaster include a lack of trained responders as well as a lack of medical recordkeeping, data collection, and established outcome measures. Additional development of health-related rehabilitation following natural disaster is urgently required.
Gesehen am 14.09.2022